The neonicotinoid thiacloprid causes transcriptional alteration of genes associated with mitochondria at environmental concentrations in honey bees. (November 2020) - Fent, Karl; Schmid, Michael; Hettich, Timm; Schmid, Simon
Abstract: Thiacloprid is widely used in agriculture and may affect pollinators. However, its molecular effects are poorly known. Here, we report the global gene expression profile in the brain of honey bee foragers assessed by RNA-sequencing. Bees were exposed for 72 h to nominal concentrations of 25 and 250 ng/bee via sucrose solution. Determined residue concentrations by LC-MS/MS were 0.59 and 5.49 ng/bee, respectively. Thiacloprid exposure led to 5 and 71 differentially expressed genes (DEGs), respectively. Nuclear genes encoding mitochondrial ribosomal proteins and enzymes involved in oxidative phosphorylation, as well as metabolism enzymes and transporters were altered at 5.49 ng/bee. Kyoto Encylopedia of Genes and Genomes (KEGG) analysis revealed that mitochondrial ribosome proteins, mitochondrial oxidative phosphorylation, pyrimidine, nicotinate and nicotinamide metabolism and additional metabolic pathways were altered. Among 21 genes assessed by RT-qPCR, the transcript of farnesol dehydrogenase involved in juvenile hormone III synthesis was significantly down-regulated. Transcripts of cyp6a14-like and apolipophorin-II like protein, cytochrome oxidase ( cox17 ) and the non-coding RNA (LOC102654625) were significantly up-regulated at 5.49 ng/bee. Our findings indicate that thiacloprid causes transcriptional changes of genes prominently associated with mitochondria, particularly oxidative phosphorylation. This highlight potential effects of this neonicotinoid on energy metabolism, which may compromise bee foraging and thriving populations at environmentally relevant concentrations. Graphical abstract: Image 1 Highlights: RNA-sequencing reveals molecular effects in brain of forager honey bees. Residues of thiacloprid in exposed bees are environmentally relevant. 0.59 and 5.49 ng thiacloprid/bee alter 5 and 71 gene transcripts, respectively. Alterations occurred for genes encoding mitochondrial proteins and enzymes. Farnesol dehydrogenase transcript encoding enzyme involved in juvenile hormone III synthesis is down-regulated. Abstract : Thiacloprid alters nuclear genes in brain encoding mitochondrial proteins.